2018
DOI: 10.15171/jrip.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

Selenium effects on antioxidant and inflammatory indices in renal ischemia-reperfusion injury in rats

Abstract: Introduction: Selenium (Se) is an antioxidant and reactive oxygen species (ROS) scavenger. Objectives: This study was conducted to evaluate the effects of Se on renal functional parameters, oxidative stress biomarkers, myeloperoxidase (MPO) activity, and the nitric oxide (NO) level in renal ischemia-reperfusion (IR) injury in rats. Materials and Methods: Twenty-four male Wistar rats (180–200 g) were selected and subsequently divided into three groups (n=8); group 1 as the control group, group 2 as the untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…This causes cell damage by producing toxic metabolites and reducing cellular energy. Also free radical generation especially reactive oxygen species (ROS) play a role in cell damage initiated by the reperfusion of blood flow to the ischemic organ [22] .…”
Section: Discussionmentioning
confidence: 99%
“…This causes cell damage by producing toxic metabolites and reducing cellular energy. Also free radical generation especially reactive oxygen species (ROS) play a role in cell damage initiated by the reperfusion of blood flow to the ischemic organ [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Selenium reduced serum creatinine, urea and MDA concentrations. GPx, GSH and SOD activity increased [19]. Based on the above studies, it can be concluded that selenium has antioxidant activity, protects nephrons, hepatocytes and cardiomyocytes, and prevents apoptosis.…”
Section: Introductionmentioning
confidence: 74%
“…Based on the above studies, it can be concluded that selenium has antioxidant activity, protects nephrons, hepatocytes and cardiomyocytes, and prevents apoptosis. The effects of selenium on organ function [1,[14][15][16][17][18][19][20] are shown in Figure 1. Research results to date suggest that selenium may potentially have a therapeutic effect as a component of preservation solutions for kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than nutritional values, selenium has an important role in human immune system [ 6 ]. Because of the antioxidant effects of selenium, it is widely used in the studies of the animal models of oxidative stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%